Síntese e caracterização de novas imidazolidinas-2,4- diona e 2-tioxo-4-ona com potencialidade para atividade biológica - Souza, Severino Araujo de (2010)
The scientific community has great interest in synthetic heterocyclic compounds because of the possibilities that these compounds contain several different biological properties. The structural changes in the imidazolidine ring may modify its chemical and physical properties, and produce biological effects with a variety of useful applications. The aim of this study was to obtain a series of hydantoins with biological activities, in which 16 derivatives synthesized. The compounds were obtained in three stages: first, we made the reaction of sodium cyanide, ammonium chloride and aromatic aldehydes in order to be replaced, followed by acid hydrolysis in order to create the Amino acids Derived of Glycine (Strecker synthesis). In the second stage, we made the reaction of the amino acids prepared with phenylisocyante and / or phenilisotiocianate followed by acid hydrolysis to form the imidazolidine derivatived and Thioimidazolidinics (HPA-03, HPA-04, HPA-05, HPA-08, HPA-09, HPA -10, 11- HPA, HPA-14). In the third and final stage, we made the reaction of the imidazolidine derivatives obtained with benzoyl chloride and / or 4-chloro benzoyl. We obtained the following compounds: IM-01, IM-02, IM-03, IM-04, IM-05, IM-06, MI-07 and MI-08. There was no any information in literature about these compounds. The structures of the synthesized compounds were characterized by the Infrared Absorption Spectroscopy and Nuclear Magnetic Resonance of Hydrogen and Carbon. Two compounds were analyzed in the central nervous system. The compound 5 - (4-etilfenil)-3-phenylimidazolidine- 2 , 4-dione (HPA-10) did not present any action in the central nervous system, and the compound 5 - (4-isopropyl)-3-phenyl-imidazolidine- 2,4-dione (HPA- 14) presented some action in the central nervous system.